2013
DOI: 10.3386/w19723
|View full text |Cite
|
Sign up to set email alerts
|

Can Non-Interest Rate Policies Stabilize Housing Markets? Evidence from a Panel of 57 Economies

Abstract: Using data from 57 countries spanning more than three decades, this paper investigates the effectiveness of nine non-interest rate policy tools, including macroprudential measures, in stabilizing house prices and housing credit. In conventional panel regressions, housing credit growth is significantly affected by changes in the maximum debt-service-to-income (DSTI) ratio, the maximum loan-to-value ratio, limits on exposure to the housing sector and housing-related taxes. But only the DSTI ratio limit has a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 2 publications
5
74
2
2
Order By: Relevance
“…29 In terms of normalizing the magnitude of these policy shocks, we pick the size of the …scal shocks so that the peak response of output is equal to that from lowering regulatory LTV by 5 percentage points (pp).…”
Section: E¤ects Of …Scal and Macroprudential Policies On Mortgage Debtmentioning
confidence: 99%
“…29 In terms of normalizing the magnitude of these policy shocks, we pick the size of the …scal shocks so that the peak response of output is equal to that from lowering regulatory LTV by 5 percentage points (pp).…”
Section: E¤ects Of …Scal and Macroprudential Policies On Mortgage Debtmentioning
confidence: 99%
“…Acolin et al 2016). Other studies have shown the effect of credit constraints, including DTI constraints, on house prices, such as and Kuttner and Shim (2016). Johnson and Li (2010) show that a high DTI is predictive of the consumer having been denied credit.…”
mentioning
confidence: 91%
“…Ayrıca makro ihtiyati politikaların asimetrik etkilerin varlığı nedeniyle piyasa başarısızlıklarını engellemede daha etkin olduğunu ortaya koymuşlardır. Kuttner ve Shim (2013), gelişmiş ve gelişmekte olan ülkeler için makro-ihtiyati araçların konut fiyatları ve kredileri üzerindeki etkisini sabit etki panel regresyon ile test etmişlerdir. Analiz sonucunda en başarılı aracın borç-gelir limiti olduğu daha sonra da borç-gelir limiti kadar olmasa da kredi-değer limitinin de etkili olduğu sonucuna varılmıştır.…”
Section: Sektörel öNlemlerunclassified